Rapamycin: A Bacteria-Derived Immunosuppressant That Has Anti-atherosclerotic Effects and Its Clinical Application - Liu, Yandong; Yang, Futang; Zou, Sili; Qu, Lefeng (Frontiers in Pharmacology, 2019)
Atherosclerosis is the leading cause of stroke and death worldwide. Although many lipid-lowering or antiplatelet medicines have been used to prevent the devastating outcomes caused by atherosclerosis, the serious side effects of these medicines cannot be ignored. Moreover, these medicines are aimed at preventing end-point events rather than addressing the formation and progression of the lesion. Rapamycin (sirolimus), a fermentation product derived from soil samples, has immunosuppressive and anti-proliferation effects. It is an inhibitor of mammalian targets of rapamycin, thereby stimulating autophagy pathways. Several lines of evidence have demonstrated that rapamycin possess multiple protective effects against atherosclerosis through various molecular mechanisms. Moreover, it has been used successfully as an anti-proliferation agent to prevent in-stent restenosis or vascular graft stenosis in patients with coronary artery disease. A thorough understanding of the biomedical regulatory mechanism of rapamycin in atherosclerosis might reveal pathways for retarding atherosclerosis. This review summarizes the current knowledge of biomedical mechanisms by which rapamycin retards atherosclerosis through action on various cells (endothelial cells, macrophages, vascular smooth muscle cells, and T-cells) in early and advanced atherosclerosis and describes clinical and potential clinical applications of the agent.